Spatial Memory Dysfunction Induced by Vitamin C Deficiency Is Associated with Changes in Monoaminergic Neurotransmitters and Aberrant Synapse Formation - Stine Normann Hansen; Anne Marie V. Schou-Pedersen; Jens Lykkesfeldt; Pernille Tveden-Nyborg (MDPI AG, 2018)
Vitamin C (vitC) is important in the developing brain, acting both as an essential antioxidant and as co-factor in the synthesis and metabolism of monoaminergic neurotransmitters. In guinea pigs, vitC deficiency results in increased oxidative stress, reduced hippocampal volume and neuronal numbers, and deficits in spatial memory. This study investigated the effects of 8 weeks of either sufficient (923 mg vitC/kg feed) or deficient (100 mg vitC/kg feed) levels of dietary vitC on hippocampal monoaminergic neurotransmitters and markers of synapse formation in young guinea pigs with spatial memory deficits. Western blotting and high performance liquid chromatography (HPLC) were used to quantify the selected markers. VitC deficiency resulted in significantly reduced protein levels of synaptophysin (p = 0.016) and a decrease in 5-hydroxyindoleacetic acid/5-hydroxytryptamine ratio (p = 0.0093). Protein expression of the N-methyl-d-aspartate receptor subunit 1 and monoamine oxidase A were reduced, albeit not reaching statistical significance (p = 0.0898 and p = 0.067, respectively). Our findings suggest that vitC deficiency induced spatial memory deficits might be mediated by impairments in neurotransmission and synaptic development.